1976
DOI: 10.1044/jshd.4103.412
|View full text |Cite
|
Sign up to set email alerts
|

Imitation: A Closer Look

Abstract: This paper explores the effectiveness of elicited imitation in clinical assessment and remediation procedures. A critical review of the literature dealing with the role of elicited imitation in language acquisition as well as the use of elicited imitation clinically is presented. Conclusions drawn from the review indicated that the effectiveness of employing elicited imitation for assessment and remediation purposes is not clearly defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 0 publications
3
4
0
Order By: Relevance
“…Detailed error analyses suggest that children’s underlying grammars guide their responses to sentence imitation tasks, as suggested by earlier studies (Prutting & Connolly, 1976; Prutting et al, 1975; Vinther, 2002) and demonstrated more recently by Smolik & Vavru (2014). The SLI and LE groups, predicted to be in a stage of optional finiteness marking, had a higher percentage of omitted finiteness markers in obligatory contexts compared to the AE group, substituted familiar verbs for unfamiliar verbs during imitation, and, when clauses were incorrectly imitated, all three groups were equally likely to change one or more components to result in a grammatically well-formed clause.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Detailed error analyses suggest that children’s underlying grammars guide their responses to sentence imitation tasks, as suggested by earlier studies (Prutting & Connolly, 1976; Prutting et al, 1975; Vinther, 2002) and demonstrated more recently by Smolik & Vavru (2014). The SLI and LE groups, predicted to be in a stage of optional finiteness marking, had a higher percentage of omitted finiteness markers in obligatory contexts compared to the AE group, substituted familiar verbs for unfamiliar verbs during imitation, and, when clauses were incorrectly imitated, all three groups were equally likely to change one or more components to result in a grammatically well-formed clause.…”
Section: Discussionsupporting
confidence: 59%
“…The development of a coding system that captures imitation accuracy for the different linguistic components included in the stimulus item (e.g., verb root imitation, finiteness marking imitation) allows the assessment of performance on each component of interest. In this way, while sentence imitation is often used as an index of verbal memory, performance on sentence imitation tasks can also be used as an index of children’s generative use of grammar such that children draw upon the grammar they have available as they hear the input clause and produce their response (e.g., Ambridge & Pine, 2006; Menyuk, 1964; Prutting & Connolly, 1976; Prutting, Gallagher, & Mulac, 1975; Smolik & Vavru, 2014; Vinther, 2002). …”
Section: Methodological Considerations: Sentence Imitation Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been found in developmental echolalia (Prutting and Connolly, 1976) and autistic echolalia (Schreibman and Carr, 1978). Stengel (1947) found that echolalia was more likely to occur when comprehension was impaired and was then frequently found in association with completion phenomena.…”
Section: Possible Mechanisms Of Echophenomenasupporting
confidence: 53%
“…The strong tendency to produce echolalic responses in transcortical sensory aphasia occurs in the context of very impaired receptive language and relative sparing of expressive language, and even nonsense or foreign phrases may be echoed (Benson, 1979). Prutting and Connolly (1976) noted that the frequency of developmental echolalic responses decreased as linguistic ability increased. Similarly, Howlin (1982) found that the incidence of echolalia was reduced in autistic children of more advanced linguistic ability.…”
Section: Possible Mechanisms Of Echophenomenamentioning
confidence: 99%